Understanding discourse in final papers from the Literature Course: (re/de)construction of teaching knowledge in academic writing practices - Fonseca, Janaína Zaidan Bicalho (Entrepalavras, 2025)
The objective of this work is to investigate the functioning of academic writing, with the purpose of understanding the discursive-textual strategies activated by the subject who writes, reflecting or hiding in their ways of saying. From the perspective of this study, such an approach would allow for reflection on the ways in which academic texts produce and disseminate knowledge in their field or, alternatively, refrain from undertaking this task. For this, I will use an undergraduate course conclusion work, whose text founds a place of speech ensured by the sayings that compose it. In other words, it is a researcher/student in training who, sometimes, keeps his writing conditioned to the critical fortune that orbits around his object of investigation. The observation in question does not neglect the process of discursive heterogeneity that constitutes each text, but problematizes its mode of incursion into a writing conditioned to academic consensus. Theoretically, this work is affiliated with the dialogical conception of language, with Bakhtin as its great exponent, and with studies on academic writing (Fonseca, 2023a, B; Barzotto, 2016; Tutin, 2014; Boch, Grossmann, 2002). Methodologically, it is committed to the procedures of analysis of the descript (Riolfi, Barzotto, 2014). The results indicate that, although the author of the undergraduate thesis seeks to reflect on literature teaching and offer recommendations for pedagogical practice, their writing tends toward depersonalization, replication of theoretical voices, and a lack of empirical evidence, especially in the initial sections. Nevertheless, there are traces of attempts at subjective insertion and autonomous reflection, particularly in the conclusion, revealing tensions between the modes of discourse and the construction of knowledge within the teacher education context.